Analisis Sosial Ekonomi dan Kesehatan terhadap Angka Kematian Bayi di Jawa Timur 2022 - Putri, Ananda Rania; Agustina, Serly; Sagita, Fauzan Faris; Kartiasih, Fitri (Seminar Nasional Official Statistics, 2024)
Infant Mortality Rate (IMR) is a key indicator of a country's health and well-being. It's frequently regarded as a marker of social advancement and human growth. As a result, eliminating IMR is a major goal in the RPJMN 2020-2024, both nationally and regionally. East Java's IMR reached 13,49 deaths per 1000 live births, exceeding the 2024 objective. The purpose of the research is to investigate how socioeconomic and health-related factors would affect AKB in East Java in 2022. Descriptive and inferential analysis using multiple linear regression were employed. The results showed that the percentage of females aged 10 and up who married before the age of 17 and the open unemployment rate had a favourable effect on IMR. Meanwhile, birth at a health care facility and life expectancy have a detrimental impact on IMR.